Tinjauan Yuridis Terhadap Pemutusan Hubungan Kerja Secara Sepihak - Nor Hafijhah; Marsella Marsella; Alvin Hamzah Nasution (JUNCTO: Jurnal Ilmiah Hukum, 2021)
Termination of work relations between workers and employers (entrepreneurs), commonly known as layoffs, can occur due to the expiration of a certain period that has been previously agreed or agreed upon and can also occur because of a dispute between the worker and the employer (entrepreneur), the death of the worker or for other reasons. As for what is meant by termination of employment according to F.X. Djumialdji, is the termination of a work relationship because of certain things that result in the termination of rights and obligations between workers or laborers and entrepreneurs. Worker Rights / labor rights. Rights are everything that must be obtained by everyone who has been there since birth, even from the womb. Workers / laborers rights are always attached to everyone who works for a salary. Because of his job. All rights and obligations of workers are clearly stated in the Civil Code, the provisions regarding the obligations of laborers / workers are regulated in Articles 1603, 1603a, 1603b, and 1603c. Settlement of cases in term of employment based on industrial relations courts is carried out using the first method outside the court (non-litigation) and the second through the PHI (litigation). Outside the court (non-litigation) include: Bipartite negotiations, tripartite negotiations. And the settlement process is limited to 50 (fifty) working days if more then it is considered broken or finished.